(untitled) (Research, Society and Development, 2020)
Objective: To analyze the therapeutic touch in integral care to the human being in the light of Ecosystem Thinking, in the nurse’s view. Method: Exploratory, descriptive, qualitative study conducted with 11 nurses, who used therapeutic touch in the daily work of professional work in different health scenarios, selected by the Snowball technique. Data were collected through semi-structured interviews and submitted to Discursive Textual Analysis. Results: Data analysis allowed us to verify that the application of therapeutic touch inte-related to the principles of Ecosystem Thinking makes it possible to care for the human being in their integrality. The elements participating in this technology, understood as a system and their subsystems, form a totality/ecosystem unit, which in continuous interrelationship with each other and with the universal energy field, produce movement and energy. This set seeks to harmonize and balance the energetic field of the human being, involving its bio-psycho-social and spiritual multidimensionalities as a whole. Conclusion: There is the possibility, when applying the Therapeutic Touch, using ecosystem principles, of providing effects of integral care to the human being and understanding it as a system, which continues to change, promoted by the interrelations of its components and with the environment, in which he lives and develops.